Variación en el presupuesto del GAD Parroquial Rural de Ricaurte durante el periodo 2020 – 2022. - Barrios Carbo, Genesis Abigail (2024)
During 2020-2022, the Rural Parish GAD of Ricaurte faced significant challenges due to variations in its financial resources. These fluctuations, caused by the economic crisis and inefficient resource management, negatively affected the implementation of essential projects and the provision of public services. The project focused on analyzing these budgetary variations to identify the underlying causes and assess the management of GAD. A descriptive approach and quantitative methods were used, analyzing budget cells and GAD financial data. Significant changes were observed in fixed assets, highlighting investment in infrastructure, while efficiency in asset use and capital-related borrowing raised areas for improvement. The analysis revealed that, while budgetary stability was adequate in 2020, significant deviations in revenue and expenditure occurred in 2021 and 2022, reflecting problems in fund-raising and project execution. These findings underscored the need for more robust financial strategies and effective planning to ensure efficient management. This study showed that the Parish GAD of Ricaurte needs effective and transparent financial management. Reducing indebtedness, increasing efficiency in the use of assets, and continuing to invest in infrastructure are some of the suggestions. These actions are crucial to ensuring sustainable and equitable development in the parish and increasing community confidence in the government.